2014
DOI: 10.1111/test.12062
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Inquiry in Statistics and Probability in the Primary Classroom

Abstract: We describe how the use of a games environment combined with technology supports upper primary children in engaging with a concept traditionally considered too advanced for the primary classes: The Law of Large Numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Some studies also suggested some new ways for enhancing statistical knowledge in young ages. Leavy and Hourigan (2015) argued that appropriate implementations supported the improvement of statistical literacy by introducing authentic statistical investigations in the lesson. For college students, Clair and Chihara (2012) implemented a pedagogical strategy, team-based learning, and revealed the effectiveness of the approach compared to the individual participation.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies also suggested some new ways for enhancing statistical knowledge in young ages. Leavy and Hourigan (2015) argued that appropriate implementations supported the improvement of statistical literacy by introducing authentic statistical investigations in the lesson. For college students, Clair and Chihara (2012) implemented a pedagogical strategy, team-based learning, and revealed the effectiveness of the approach compared to the individual participation.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of hands-on activities to develop students' intuitive thinking about the law of large numbers. For examples of these activities, see Dinov et al (2009), Falk andLann (2015) and Leavy and Hourigan (2015). This activity also provides teachers a hands-on example to illustrate this concept in practice.…”
Section: Assigning Pointsmentioning
confidence: 98%
“…For examples of these activities, see Dinov et al . (), Falk and Lann () and Leavy and Hourigan (). This activity also provides teachers a hands‐on example to illustrate this concept in practice.…”
Section: Pig Activity Descriptionmentioning
confidence: 99%
“…The researchers' selection of the topics was informed by international curricula and the recommendation of professional bodies. Each group was given a particular probability concept that would be presented to students in the following sequence: describing likelihoods, comparing and explaining likelihoods and ordering likelihoods of events and the Law of Large Numbers (Leavy and Hourigan ). This article focuses on the second of these: comparing and explaining likelihoods.…”
Section: Research Contextmentioning
confidence: 99%
“…The challenge for teachers is not merely to provide more experiences in probability for younger learners but also to provide meaningful experiences, which promote correct and robust understanding of concepts. Hence, when designing pedagogical experiences relating to probability, educators need to take into account the importance of prerequisite mathematical understandings, the presence of naïve understandings and biases relating to probability and the ways in which everyday meanings of probabilistic terms may pose challenges for the development of understanding (Greer and Mukhopadhyay ; Kaplan et al ; Leavy and Hourigan ; Lecoutre ).…”
Section: Introductionmentioning
confidence: 99%